The concept of production resources in agricultural sector and their classification in the case of Uzbekistan - Abduaziz Abduvasikov; Madina Khurramova; Hafizov Akmal; Panjieva Nodira; Jakhongir Kenjabaev; Dilshod Anarkulov; Shoirakhon Kosimova; Karjavova Xurshida; Mavlyanova Dildora; B. Sapaev; Suluv Sullieva; Zokirov Kurbonalijon (Caspian Journal of Environmental Sciences)
The paper focuses on the institutional shifts in agricultural relations that establish the prerequisites for raising production efficiency in the context of agriculture's transition. It was investigated how quickly and qualitatively new structural and market reforms could be introduced in the agricultural sector. Sustainability and organizational development of state assistance that is effective in the face of market volatility and development transformation processes is predicated on the enhancement of the mechanism. Agriculture-related subsidies, the application of resource-saving technology, and specifically the efficacy of water-saving technologies were examined.